2020
DOI: 10.1088/1742-6596/1539/1/012088
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Team Assisted Individualization (TAI) based Assessment for Learning (AfL) in Student’s Mathematical Reasoning Ability of Junior High School

Abstract: This research aims (1) to examine the completeness of classical learning classroom with learning model Team Assisted Individualization based Assessment for Learning, and (2) to examine the comparison of the ability of student’s mathematical reasoning with learning model Assisted Individualization based on Assessment for Learning and direct learning model. This research uses a quasi experimental design method with posttest-control-group design. The population in this study was the regular students of grade VIII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, most of these studies have not comprehensively investigated specific aspects. For example, Argianti, et al [17] showed in their study that the application of the TAI learning model improved mathematical reasoning ability in junior high school students, outperforming the results obtained from the direct learning model. Similar conclusions were also found by Arrahim, et al [21], who highlighted the improvement of students' conceptual understanding at the elementary school level through the application of the TAI model.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, most of these studies have not comprehensively investigated specific aspects. For example, Argianti, et al [17] showed in their study that the application of the TAI learning model improved mathematical reasoning ability in junior high school students, outperforming the results obtained from the direct learning model. Similar conclusions were also found by Arrahim, et al [21], who highlighted the improvement of students' conceptual understanding at the elementary school level through the application of the TAI model.…”
Section: Discussionmentioning
confidence: 98%
“…The practice of cooperative learning has many advantages for the development of intellectual and social skills. One of the main aspects emphasized is listening to classmates' opinions and applying logic to conclusions, resulting in more comprehensive thinking for students [17]. In addition, cooperative learning models also have the potential to promote cooperation and collaboration among students with diverse backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…The TAI in cooperative type was beneficial the students in combining their individual and group learning models. The deleivered thematic subjects were empirically to comprehend with a high enthusiasm and conduciveness among students [29]. Generally, students' reasoning ability with this TAI learning were connected with their assessment for learning model that also thoroughly gained the classical completeness better than the direct learning model [30].…”
Section: Introductionmentioning
confidence: 99%
“…Since lifelong learning has been advocated in modern society, more emphasis should be laid on the cultivation of SIL. For students, in order to realize their ideals, they should perform individual learning based on their own conditions, and the requirement satisfaction of SIL plays a key role in lifelong learning and the realization of personal values [8][9][10][11][12][13][14]. Individual learning can motivate students' learning initiative and urge them to choose the learning plans and strategies that are suitable for their current cognition level.…”
Section: Introductionmentioning
confidence: 99%